Community Empowerment Based on Good Tourism Governance in the Development of Tourism Destination (Case Study of Kawah Ijen Tourism Buffer Zone "Kampung Kopi" Gombengsari Village, Kalipuro District, Banyuwangi Regency) - Dedy Wahyu Hernanda; Lely Indah Mindarti; Riyanto Riyanto (Journal of Indonesian Tourism and Development Studies, 2018)
One form of the current trend in community empowerment is empowerment through tourism. Banyuwangi endeavor to develop the leading tourism attraction and tourism buffer. One of the buffer tourism developed in Ijen Crater Zone is Kampung Kopi (Coffee Village) Gombengsari Kalipuro District, Banyuwangi. This research used qualitative method with the type of research used a descriptive case study. In data collection, researchers used observation, interview, documentation and triangulation techniques. The analysis of case study data was carried out from reading transcripts/field notes, finding common findings and taking special findings, theoretical dialogue, triangulation of data and concluding the results of the study. The results of this study indicated that the empowerment program was conducted to change and increase community awareness, knowledge and skills in order to achieve local independence while utilizing existing local potential. The implementation of tourism management in Kampung Kopi Gombengsari is based on several principles described as follows: a) Engagement of all Stakeholders; the actors involved are classified into five actors (Government, private, community, academia, and media) or called as the Pentahelix Model, b) Continuous resource utilization and avoid the irreversible use of non-renewable resources, c) Advocating the value of local culture through the festival. Internal supporting factor for Kampung Kopi Gombengsari is various tourism potential. The external supporting factor is local government, NGOs, and other tourism actors’ support. The internal inhibiting factor is the level of education and the emergence of tourism business competition. External Inhibitors involved road infrastructure which requires improvement, bureaucratic structure and tendencies.Keywords: Community Empowerment, Good Tourism Governance, Tourism Destination Development.